Thoracic Injuries in Cats with Traumatic Fractures - Griffon, Dominique J.; Walter, Patricia A.; Wallace, L. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
The medical records of 93 cats with traumatic fractures were examined to study the pattern of thoracic trauma and establish a possible relationship between specific patterns of skeletal trauma and the prevalence of thoracic wall and pulmonary injury. Radiographic evidence of thoracic trauma was identified in 38.7% of these cats. Cats with fractures cranial to T13 were significantly more likely to sustain thoracic trauma (58%) compared to those suffering a fracture caudal to LI (25%). Cats involved in motor vehicle accident were more likely to have radiographic evidence of thoracic trauma (52%) compared to those injured by other means (22%). Forty percent of cats with radio-graphic evidence of thoracic injury did not show any clinical sign.In a retrospective survey of 93 cats admitted for evaluation of traumatic fractures, 36 cats (38.7%) had radiographic evidence of thoracic trauma. The most common thoracic injuries were lung contusion (66.6%) and pneumothorax (36%). Forty percent of the cats, with radiographic abnormalities, did not show clinical signs suggestive of thoracic injury.
Keywords: Thoracic trauma in cats; fracture pattern